Synthesis of V2O5 microspheres by spray pyrolysis as cathode material for supercapacitors. (16th March 2018) - Yin, Zhendong; Xu, Jie; Ge, Yali; Jiang, Qiaoya; Zhang, Yaling; Yang, Yawei; Sun, Yuping; Hou, Siyu; Shang, Yuanyuan; Zhang, Yingjiu
Abstract: Vanadium oxide (V2 O5 ) microspheres have attracted considerable attention in the energy field due to their unique properties such as high stability and electrochemical activity. Here, massive V2 O5 microspheres with smooth surface, hollow cavity and uniform particle sizes (0.4–1.5 μ m), were synthesized by a facile spray pyrolysis process. Post-treatment at predefined temperatures effectively turned the microsphere shell into stacked nanorods with widths of 100 nm and lengths of 500 nm when processed at 500 °C for 3 h under nitrogen atmosphere, with enhanced crystallinity. When applied as cathode materials for supercapacitors, the post-treated V2 O5 microspheres at 500 °C exhibited improved specific capacitance and longer discharge time. This is an effective method to manufacture massive V2 O5 microspheres with tailored structure and potential applications in high-performance energy storage materials.